2013
DOI: 10.1016/j.jtrangeo.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Landscape pattern and car use: Linking household data with satellite imagery

Abstract: Abstract:Landscape pattern has long been hypothesized to influence automobile dependency.Because choices about land development tend to have long-lasting impacts that span over decades, understanding the magnitude of this influence is critical to the design of policies to reduce emissions and other negative externalities associated with car use. Combining household survey data from Germany with satellite imagery and other geo-referenced data sources, we undertake an econometric analysis of the relation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
1
9
0
2
Order By: Relevance
“…Across a wide variety of methodological approaches, and at the county, city, neighborhood, and household levels, higher income correlates with higher car ownership and use (for a diverse range of methodologies and units of analysis, see Ingram and Liu, 1999;Holtzclaw et al, 2002;Keller and Vance, 2013;Newman and Kenworthy, 2006;Potoglou and Kanaroglou, 2008). At the correct unit of analysis-generally thought to be the household or individual-income is usually the strongest predictor of car ownership (for examples from a range of geographies and contexts, see Zhang, 2004;Bento et al, 2005;Dissanayake and Morikawa, 2010;Zegras, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Across a wide variety of methodological approaches, and at the county, city, neighborhood, and household levels, higher income correlates with higher car ownership and use (for a diverse range of methodologies and units of analysis, see Ingram and Liu, 1999;Holtzclaw et al, 2002;Keller and Vance, 2013;Newman and Kenworthy, 2006;Potoglou and Kanaroglou, 2008). At the correct unit of analysis-generally thought to be the household or individual-income is usually the strongest predictor of car ownership (for examples from a range of geographies and contexts, see Zhang, 2004;Bento et al, 2005;Dissanayake and Morikawa, 2010;Zegras, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Household car ownership decreases within creased built environment density [6,[19][20][21][22][23]. Diversity is negatively correlated with car ownership [6,8,[22][23][24][25][26]. Ewing et al [21] and Hong et al [25] found that road network density is also negatively correlated with household car ownership; however, the effect of design on car ownership is weaker than the effects of density and diversity [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, most empirical studies have focused on the relationship between the built environment and car ownership. Household car ownership decreases within creased built environment density [6,[19][20][21][22][23]. Diversity is negatively correlated with car ownership [6,8,[22][23][24][25][26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The urban horizontalization and sprawl, a result of low constructed densities, increases the distances of daily mobility as well as decreases the efficiency of public transportation systems, which require demand agglomeration to enable high capacity systems [10,21,22]. Such context aligns one of the factors that makes individuals prefer motorized modes of mobility, and it is one of the causes of traffic saturation in central roads [23].…”
Section: Washingt Located In Estimated Pomentioning
confidence: 99%